Kaposi sarcoma–associated herpesvirus miRNAs suppress CASTOR1-mediated mTORC1 inhibition to promote tumorigenesis - Li, Tingting; Ju, Enguo; Gao, Shou-Jiang (The Journal of Clinical Investigation, 2019)
Cytosolic arginine sensor for mTORC1 subunits 1 and 2 (CASTOR1 and CASTOR2) inhibit the mammalian target of rapamycin complex 1 (mTORC1) upon arginine deprivation. mTORC1 regulates cell proliferation, survival, and metabolism and is often dysregulated in cancers, indicating that cancer cells may regulate CASTOR1 and CASTOR2 to control mTORC1 signaling and promote tumorigenesis. mTORC1 is the most effective therapeutic target of Kaposi sarcoma, which is caused by infection with the Kaposi sarcoma–associated herpesvirus (KSHV). Hence, KSHV-induced cellular transformation is a suitable model for investigating mTORC1 regulation in cancer cells. Currently, the mechanism of KSHV activation of mTORC1 in KSHV-induced cancers remains unclear. We showed that KSHV suppressed CASTOR1 and CASTOR2 expression to activate the mTORC1 pathway. CASTOR1 or CASTOR2 overexpression and mTOR inhibitors abolished cell proliferation and colony formation in soft agar of KSHV-transformed cells by attenuating mTORC1 activation. Furthermore, the KSHV-encoded miRNA miR-K4-5p, and probably miR-K1-5p, directly targeted CASTOR1 to inhibit its expression. Knockdown of miR-K1-5p and -K4-5p restored CASTOR1 expression and thereby attenuated mTORC1 activation. Overexpression of CASTOR1 or CASTOR2 and mTOR inhibitors abolished the activation of mTORC1 and growth transformation induced by pre–miR-K1 and -K4. Our results define the mechanism of KSHV activation of the mTORC1 pathway and establish the scientific basis for targeting this pathway to treat KSHV-associated cancers.